Predictive factors of return to activity in elderly patients operated on for a fracture of the lower limb: a study of 113 patients - GOUKODADJA, OSWALD; PADONOU, ADEBOLA; Akpamoli, Ivanne; Adendjingué, Daniel; Dossou, Cédric; CHIGBLO, Pascal; HANS MOEVI AKUE, KPAKPOVI C. I. ARISTOTE (My University, 2023)
Background: The aim of this study was to determine the factors predictive of resumption of activity in elderly subjects operated on for a fracture of the lower limb. Methods: This was a cross-sectional study with retrospective data collection in subjects aged 56 and over who had undergone lower-limb surgery with a minimum follow-up period of six months. Patients' walking autonomy was assessed using the Parker score. The modular integrated household survey on living conditions was used to assess patients' socio-economic status. Bivariate analysis was performed using the chi-square test and the calculation of measures of association. Results: The series included 113 patients with a mean age of 70±9.54 years and a sex ratio of 1.09. Fractures of the upper end of the femur predominated in 67.6% of cases. The most common surgical procedure was intermediate hip replacement in 30 patients (26.5%). Rehabilitation sessions were performed in 95 patients (84.1%). The postoperative Parker score at the last follow-up was 9/9 in 41 patients (36.3%). Resumption of educational and productive activities and interpersonal responsibilities was achieved in 90 patients (79%). Significant associations (p<0.05) were found between resumption of activities and age, sex, marital status, history of arterial hypertension, psychiatric history, preoperative Parker score, postoperative Parker score and return to a private residence. Conclusions: Older age, female gender, absence of a partner, high blood pressure, non-personal residence and poor Parker score are factors with a poor prognosis for return to activity
Keywords: Elderly subject; Return to activity; Lower limb